2007
DOI: 10.1542/peds.2006-1434
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine Use in Children and Adolescents With Familial Mediterranean Fever: Literature Review and Consensus Statement

Abstract: The daily application of colchicine is the standard therapy for prophylaxis of attacks and amyloid deposition in familial Mediterranean fever. However, because of many issues (eg, dosage, time of introduction, etc), no standardized treatment recommendations have been established. In this work we review the available literature on colchicine use with respect to its indication, efficacy, mode of application, and safety in children and adolescents with familial Mediterranean fever. On the basis of this analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
158
1
39

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(203 citation statements)
references
References 114 publications
2
158
1
39
Order By: Relevance
“…Colchicine can be given to children with the disease even before the age of 1 year. It was shown that children younger than 5 years of age might need colchicine dosages ranging from 0.03 to 0.07 mg/kg/day (42). Children weighing more than 10 kg can take 1 mg of colchicine daily.…”
Section: Treatment Of Fmfmentioning
confidence: 99%
“…Colchicine can be given to children with the disease even before the age of 1 year. It was shown that children younger than 5 years of age might need colchicine dosages ranging from 0.03 to 0.07 mg/kg/day (42). Children weighing more than 10 kg can take 1 mg of colchicine daily.…”
Section: Treatment Of Fmfmentioning
confidence: 99%
“…In most of the cases, treatment with colchicine to prevent attacks of fever and systemic amyloidosis is very effective (15). In general, continuous treatment with colchicine is more effective than intermittent treatment during attacks.…”
Section: Discussionmentioning
confidence: 99%
“…Almost 5% of patients did not respond to this treatment. [9,10] The dose of colchicine used varied between 1 to 2 mg/day. Prior studies reported that 0.5 mg/day of colchicine in children <5 years of age, 1 mg/day for children between five and 10 years of age, and 1.5 mg/day for children >10 years of age was successful in the majority of children.…”
Section: Discussionmentioning
confidence: 99%
“…[11,12] Failure to respond to 2 mg/day usually predicts a failure of higher doses which also increases the risk of drug toxicity. [10,13] Substantial subclinical inflammation occurs widely and over prolonged periods in patients with FMF, [14] and young patients with chronic inflammatory disease are predisposed to associated growth retardation. Serum amyloid A (SAA) is sensitive for detecting inflammation in such patients.…”
Section: Discussionmentioning
confidence: 99%